Student Motivation in CORONAPOLIS: Effects of Transactional Distance Perceptions on EFL Undergraduate Students’ Motivation - Takkaç Tulgar, Ayşegül (GIST – Education and Learning Research Journal, 2022)
The concept of Transactional Distance (TD) experienced in distance education has been recorded as a focal point in many studies examining its effects in various dimensions in different courses. However, there is scarcity of research on TD in relation to learner motivation in language learning. This exploratory case study investigated TD perceptions of EFL (English as a Foreign Language) undergraduates participating in distance education courses held at a Turkish university within the boundaries of CORONAPOLIS, an imaginary city which is under the threat and destructive effects of Covid-19 pandemic. Specifically, this study examined the effects of TD perceptions on the motivation of 87 EFL students. The data were collected through the participants’ informal self-reports and open-ended questions. The results of the content analysis showed that the participants had varying perceptions of the dimensions of TD; dialogue, structure and autonomy. The results also showed that they had different motivational experiences in relation to their perceptions. In the light of the results, some pedagogical implications are made.